2016
DOI: 10.1016/j.msea.2015.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic emission study on the activity of slip and twin mechanisms during compression testing of magnesium single crystals

Abstract: Magnesium single crystals with various crystallographic orientations were uniaxially and channel-die compressed at room temperature (RT) and at a constant strain rate of 10-3 s-1 in order to obtain a comprehensive set of acoustic emission (AE) data, which can be applied in studies of twinning and dislocation processes in polycrystalline Mg alloys. Loading along the <11.2> axis led to a preferable activation of basal slip and it was accompanied by a low amplitude AE signal. Twinning was exclusively observed dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…Twin nucleation produces large amplitude AE signals and thus belongs to excellent sources of AE. [21,29] Consequently, the maximum in the AE count rate observed at the macroscopic yield point could be related to intensive twin nucleation and collective dislocation movement. The following decrease in the AE activity can be explained by reducing the mean free path of the dislocations due to increasing number of nucleated twins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Twin nucleation produces large amplitude AE signals and thus belongs to excellent sources of AE. [21,29] Consequently, the maximum in the AE count rate observed at the macroscopic yield point could be related to intensive twin nucleation and collective dislocation movement. The following decrease in the AE activity can be explained by reducing the mean free path of the dislocations due to increasing number of nucleated twins.…”
Section: Discussionmentioning
confidence: 99%
“…Deformation kinks are formed by basal dislocations, which produce generally low AE. [29] Moreover, they are activated at higher stress levels, where high dislocation density within the material reduces the AE activity. [29,33] It was also shown that the stacking faults suppress dislocation slip and enhance dislocation accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the growth or thickening of twins, detwinning or thinning is basically a movement of twin boundaries, so no detectable AE signal [31,36,37] is expected as a result of this mechanism.…”
Section: General Findings During Pre-compression and Reverse Tensile mentioning
confidence: 99%
“…AE is a powerful method for revealing the active deformation mechanisms and their development during loading. The AE technique was successfully used to investigate various metallic materials, especially with an hcp lattice, as it is highly sensitive to twin nucleation.…”
Section: Introductionmentioning
confidence: 99%